Architectural framework for mobile multicast support in wireless mesh networks - Sanni, Mistura L.; Hassan Abdalla Hashim, Aisha; Hassan, Wan Haslina; Anwar, Farhat; Naji, Ahmed Wathik; Mahmoud Ahmed, Gharib Subhi (Thailands National Science & Technology Development Agency, 2013)
A wireless mesh network (WMN) is an infrastructure multihop ad hoc network with broadband capabilities. Multicasting is an efficient mechanism for delivery of group communication. However, the current IEEE 802.11s standard has no provision for efficient group communication delivery. Furthermore, the disruption in internet connectivity and loss of information when a mobile mesh client changes its point of attachment may lead to disruption in an ongoing session. The internet gateway (IGW), a prominent component, serves as the wired bridge between the mesh nodes and the internet, thus its placement determines the overall quality of communication in WMNs. Accordingly, a structural design for supporting multicast services in this architecture is indispensable. The main question this paper addresses is how multicast can be efficiently supported for mobile mesh clients in WMN architecture. This paper adopts the technique of employing multicast architecture to solve mobility problems for mobile mesh clients. Thus a framework of novel architecture for supporting multicast services for group application delivery over WMN is presented. The proposed architecture features enhanced functionality of IGW, shared multicast tree, optimal design for IGW and core placement, hierarchical mobility management, load balancing, and robustness. The overall objective is the provision of cost efficient WMN architecture while mobile multicast traffic delivery is supported optimally. This is the first effort reporting multicast service support framework for mobile mesh clients with a focus on IGW placement and functionality.